Stuttering in children - a literature review update - Mónica Soares Rocha (Cadernos de Saúde, 2019)
Introduction: Stuttering is a fluency disorder in which the flow of speech is disrupted. The disorder is frequently misunderstood and to better analyze it is necessary to understand stuttering as more than a speech problem. Recent literature points out thatshould instead be viewed as a communication disorder with the potential to affect several aspects of children’s lives.  Different perspectives about stuttering can bring a more diverse analysis and move the field forward in scientific knowledge, however, it can also lead to fragmented and controversial views. Despite some lingering scientific consensus issues, there has been growing agreement among researchers that stuttering is a multifactorial disorder. Aim: To summarize and analyze previously published research considering stuttering as a dynamic disorder influenced by several factors. Materials and Methods: A comprehensive review which focuses on the development of stuttering, and the implications for the onset, manifestation, and chronicity of this disorder in school-age children who stutter. Results: Because of the ever-increasing literature in the area of stuttering, the review addresses assessment procedures and the perception of the impact of stuttering on children’s daily life. Conclusion: This comprehensive view contributes to an updated understanding of therapeutic and scientific factors to be considered in the evaluation and treatment of stuttering.